Personal Income Tax Reliefs in Poland as An Instrument of Counteracting The Impact of COVID-19 Pandemic – Legal Aspects - Mateusz KOWALSKI (Communications of International Proceedings, 2021)
The COVID-19 pandemic, an unprecedented health and economic crisis, prompted governments worldwide, including Poland, to take legislative measures to mitigate the negative social and economic impacts of the pandemic. The aim of the paper is to present the implications of those measures in one particular area, that is the tax law. To achieve that, personal income tax relief measures adopted by the Polish government to remedy the pandemic effects were analyzed. The research was based on doctrinal analysis and the study of law method. It led to the conclusion that relief measures adopted by the Polish legislator are appropriate, but inadequate in the specific context. The most important measures adopted in Poland are emergency tax reliefs in form of tax exemptions and allowances correlated with other forms of pandemic-related aid. However, tax reliefs are predominantly addressed at taxpayers who conduct business, neglecting a portion of the society. Tax reliefs, as the research demonstrates, should definitely be extended to incorporate personal income tax payers.
Keywords: Personal income tax; tax reliefs; Covid-19